The future of fiscal federalism - Vito Tanzi (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2008)
To predict the future it is always useful to study the past. The past can help us understand how the world evolved and might suggest possible developments for the future. However, the past must be considered a reference point, or a marker, and not an anchor. To see the future as the mirror image of the past is to ignore that progress and evolution always imply change.
Keywords: 330